Biological Kerker Effect Boosts Light Collection Efficiency in Plants; Nano Letters; Vol. 19, iss. 10 - Barhom H. Hani; Machnev A. A. Andrey; Noskov R. E. Roman; Goncharenko A. A. Aleksandr Aleksandrovich; Gurvitz E. A. Egor; Timin A. S. Aleksandr Sergeevich; Shkoldin V. A. Vitaly; Koniakhin S. V. Sergei; Koval O. Yu. Olga; Zyuzin M. V. Mikhail; Shalin A. S. Aleksandr; Shishkin I. K. Ivan; et al. (2019, 2019)
Title screen